Mestrado profissional em ensino na saúde: avaliação do internato em clínica médica do curso de médico da FAMED na perspectiva do estudante - Araújo Sobrinho, Manoel Correia de (2016)
The academic work of the conclusion of the course consists of two obrigatory objects: one scientific article, originating from a developed survey in the field of work of the degree and, a technical archaic product for a demand of the results of the survey. The study that produced the scientific article had as an objective to evaluate the internship in Medical Clinic 2 from the Course of Medicine at Universidade Federal de Alagoas in the Perspective of the Student. It is about a descriptive rising, of quantitative nature, in a cohort that characterized a field study, applied to a scenario of practicum of the internship of Medical Clinic, involving sixty-one students. An instrument of perception of the Likert kind, depicting five dimensions: 1) vision of the importance and pertinence of the internship in medical clinic; 2) competencies for the attention to adult and senior citizen health; 3) relationship competencies; 4) competencies for management in health; 5) competencies for health education. The results manifest in a comfort zone, or rather, that the internship enabled opportunities of growth of the competencies for the attention in health and education in health. The relationship competency manifested as the most critical area of the internship. From these results, a planning of an event was created together with the advisors, with the intention to better inform and discuss the conclusions of the survey in the search of decisions that contribute to a better education for the students. As routing of the meeting was formalized, a proposal for Agenda de Reuniões Mensais in CLM, under the responsibility of FAMED, that was called “Agenda de encontros integradores” (technical product 2). The moment for presentation of the results was an initiative that qualified the realized survey, making possible the self-criticism and favoring an atmosphere of efficient and healthy learning. Additionally, it allowed to reach the purposes of the Mestrado Profissional demonstrating an opportunity of a critical and transforming assessment in the spaces of educational practice.